Some diagnostic properties of reconfigurable integrated circuits with boundary scan - Kern, Jerzy (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents a solution of the self-diagnostic problem of digital system by application of reconfigurable integrated circuits and boundary scan architecture. The implemented method of Built-In Self Test (BIST) is non-concurrent one and bases on the reconfiguration of the digital system, when the test mode has to be introduced. The author, with a microcontroller system as an example, shows an idea of improving the system diagnosability with minimum hardware overhead, by introducing reprogrammable gate arrays (FPGA) with modified functions, including adaptable BIST functions.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka